Penatalaksanaan Implan dengan Screw Cement Retained Prosthesis - Kusuma, Belinda; Suwandi, Trijani (Jurnal Kedokteran Gigi Terpadu, 2023)
Dental implant is currently the best choice of treatment to restore mastication, aesthetics, and phonetics functions. Dental implant is a biocompatible screw-like titanium fixture that is surgically placed into the jawbone, enabling the replacement of missing teeth that is more aesthetically biomimetic and comfortable. The recent dental implant is based on the concept of osseointegration, meaning that the implant material could naturally and predictably bond with bone. In the first case, a 28-year-old male patient with missing tooth 46 was rehabilitated with Strauman Blt implant. In the second case, a 66-year-old- female patient is missing tooth 46 and was rehabilitated with BTK implant. Both of the cases used screw-retained metal porcelain crown. Both patients did not have any systemic disease. One should comprehend the basic knowledge of implant before doing the placement to achieve maximal result. Both of the two cases were done successfully without any difficulties and no complaint post 4-month insertion.